The Development of Physics Lesson Plan with Doscovery Learning Model Assisted by Software Lectora Inspire - Eka Wahyuni; Andi Marwanti Panre; Gusti Made Veni Friandari; Hunaidah Hunaidah; Erniwati Erniwati (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2019)
The objective of the study is to find out wheter or not a Lesson Plan (RPP) was feasible to used, it is developing Lesson Plan of discovery learning assisted by lectora inspire software in the sound and light wave subjects at high school level was valid, practical and effective to used in the learning teaching process. The Lesson Plan) was validated by 3 experts of education and 3 experts of IT. The samples of this research were class XI MIPA5 Senior High School of 5 Kendari consisted of 20 students. To collected the data, the researcher was gave observations and questionnaires and the material about the feasibility of learning, student activities, teacher responses, student responses and test descriptions. To analysed the data, the researcher used descriptive quantitative. The result showed that the validation of the Lesson Plan of discovery learning assisted by lectora inspire software in the sound and light subject wave developed, based on Lesson Plan expert of education got a very valid category as indicated by the final agreement index value of 4.80 and another one by expert of Information and Technology said that the final agreement index reaching 4.05, means that the Lesson Plan was very valid. Second, the Lesson Plan by lectora inspire software was stated to be practical as indicated by the implementation of learning in each meeting and find out a very good category with the final agreement index was 3.75 and the activity of students was increasing of categories. Third, the Lectora Inspire Software assisted lesson plan was declared effective as indicated by the results of student and teacher responses, as well as students' completeness test scores obtained from the results of high n-gain analysis